Pengaruh Harga Dan Kualitas Layanan Terhadap Kepuasan Konsumen Menggunakan Jasa Travel CV.Sinar Wisata - Hadif Pebri Aparis; Lucy Chairoel (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect of price and service quality on customer satisfaction of CV. Sinar Wisata travel service users. The phenomenon of fluctuating customer numbers and preliminary surveys indicate dissatisfaction with price and service aspects. This research uses a quantitative method with data collected through questionnaires distributed to 120 respondents who have used CV. Sinar Wisata's services. Data analysis was conducted using multiple linear regression, validity and reliability tests, as well as classical assumption tests such as normality, multicollinearity, and heteroscedasticity. The results show that price has a positive and significant effect on customer satisfaction. Likewise, service quality also partially has a positive and significant effect. Simultaneously, price and service quality significantly affect customer satisfaction. This indicates that the more affordable the price and the better the quality of service provided, the higher the level of customer satisfaction. Therefore, CV. Sinar Wisata needs to maintain and improve competitive pricing and service quality standards to ensure customer loyalty.